Low-voltage NMOS-based current differencing buffered amplifier and its application to current-mode ladder filter design - Tangsrirat, W.; Klahan, K.; Dumawipata, T.; Surakampontorn, W. (My University, 2006)
An integratable circuit technique to realize a low-voltage current differencing buffered amplifier (CDBA) is introduced. The realization scheme is through the modification of a low-input resistance CCII+ and the proposed CDBA can operate with the minimum supply voltage of ±1.25∈V. In order that the signal path consists of only NMOS transistors, a negative current mirror using NMOS transistors is employed. With standard 0.5∈μm CMOS process parameters, PSPICE simulation results show that the proposed CDBA provides the terminal resistance of , , and the -3∈dB bandwidth of about 500∈MHz. Application examples employing the proposed CDBA as active elements in the leapfrog simulation of current-mode ladder filters are also included.
Keywords: Current differencing buffered amplifier; Current mode circuit; Ladder filter; NMOS transistor